48.2: Invited Paper: High conductivity & transparent aluminum‐based multi‐layer source/drain electrodes for thin film transistors. (28th November 2018) - Yao, Rihui; Zhang, Hongke; Zheng, Zeke; Li, Xiaoqing; Zhang, Xiaochen; Fang, Zhiqiang; Ning, Honglong; Deng, Yuxi; Peng, Junbiao
Abstract : In this work, transparent thin film transistors (TFTs) using multi‐layer aluminum‐doped ZnO(AZO)/Al/AZO/Al/AZO, multi‐layer AZO/Al/AZO, single AZO source/drain (S/D) electrodes were fabricated by room temperature processes on glass substrate. The conductivity, transmittance of S/D electrode films were optimized by the insertion of two 4‐nm‐thick Al layer between the AZO layers. The resistivity of the S/D electrode films decreased from 3.34×10 −3 Ω·m to 6.64×10 −5 Ω·m and the transmittance higher than 84%. The electrical properties and optical properties of these transparent TFTs were investigated in this paper. The lower work function showed a significant effect on enhancing mobility, increasing on‐state current and output current. As a result, The TFT using the AZO/Al/AZO/Al/AZO S/D electrodes exhibit a saturation mobility of 2.64 cm 2 /Vs, an Ion /Ioff radio of 2.52×10 6, a subthreshold swing of 1.14 V/decade, and a transmittance of 71.37%. The successful high‐transparent TFTs with less Indium and less thermal annealing treatment brings industry a step closer to realizing inexpensive, flexible, transparent and green displays.